Diabetes Care in Brazil - Walmir F Coutinho; Wellington Santana Silva Júnior (Ubiquity Press, 2016)
Background The diabetes epidemic affects most countries across the world and is increasing at alarming rates in Latin America. Nearly 12 million individuals have diabetes in Brazil, and the current prevalence ranges from 6.3% to 13.5%, depending on the region and the diagnostic criteria adopted in each study. Objective To provide an overview of diabetes care in Brazil, focusing on studies of diabetes epidemiology, prevalence of patients within the standard targets of care, and economic burden of diabetes and its complications. Methods SciELO and PubMed searches were performed for the terms "diabetes," "Brazil," "Brazilian," and "health system"; relevant literature from 1990 to 2015 was selected. Additional articles identified from reference list searches were also included. All articles selected were published in Portuguese and/or English. Findings Recent studies detected a prevalence of gestational diabetes mellitus of nearly 20%. Among patients with type 1 diabetes, almost 90% fail to reach target of glycemic control, with less than 30% receiving treatment for both hypertension and dyslipidemia. More than 75% of patients with type 2 diabetes are either overweight or obese. Most of these patients fail to reach glycemic targets (42.1%) and less than 30% reached the target for systolic and diastolic blood pressure, body mass index, or low-density lipoprotein cholesterol. Only 0.2% of patients reach all these anthropometric and metabolic targets. Conclusions Brazil is the fourth country in the world in number of patients with diabetes. Regardless of the diabetes type, the majority of patients do not meet other metabolic control goals. The economic burden of diabetes and its complications in Brazil is extremely high, and more effective approaches for preventions and management are urgently needed.